Coupled role of in-situ reactions and post-production pressing on the characteristics of hot-pressed aluminium-Y2O3-Al2O3 composites - Cingoz, Umut Can; Sonmez, Beyza; Kisasoz, Burcin Ozbay; Bayrak, Yahya; Kisasoz, Alptekin (ELSEVIER SCI LTD, 2026)
In this study, the combined effect of in-situ phases and post-production pressing on the characteristics of hot-pressed Al-Y2O3-Al2O3 samples was investigated. The samples were fabricated by hot-pressing route at 600 degrees C under a processing pressure of 200 MPa for 30 min. Aluminium-Y2O3 composites contained 5 wt% Y2O3, while Al-Y2O3-Al2O3 hybrid composites with the same Y2O3 content were produced using pre-oxidized matrix powder. Moreover, for each processing condition, samples were pressed at 200 MPa during cooling to reveal the effect of post-production pressing. The Al2Y4O9 and Al5Y3O12 in-situ phases were observed in the microstructure of the Al-Y2O3 and Al-Y2O3-Al2O3 composites, respectively. Furthermore, it was determined that post-production pressing promoted the formation of in-situ phases for both samples. It was observed that combined effect of Al2O3 presence and post-production pressing improved the hardness of the samples. The hardness value of Al-Y2O3-Al2O3 composite enhanced to 65.46 HV by post-production pressing. On the other hand, presence of Al2O3 in the hybrid-reinforced composites improved corrosion behavior. It was determined that Al5Y3O12 in-situ phase was more effective than Al2Y4O9 to obtain increased corrosion behavior in composites.
Keywords: Hot pressing (A); Composites (B); Corrosion (C); MECHANICAL-PROPERTIES; ALUMINUM; YTTRIUM; Y2O3; AA; Materials Science